Targeting inflammation as a treatment modality for neuropathic pain in spinal cord injury: a randomized clinical trial. Issue 1 (December 2016) - Allison, David; Thomas, Aysha; Beaudry, Kayleigh; Ditor, David
Abstract Background The purpose of the present study was to examine the effectiveness of an anti-inflammatory intervention as a treatment for neuropathic pain following spinal cord injury (SCI). Methods This randomized, parallel-group, controlled clinical trial (NCT02099890) examined 20 participants with varying levels and severities of SCI, randomized (3:2) to either a 12-week anti-inflammatory diet, or control group. Outcome measures consisted of self-determined indices of pain as assessed using the neuropathic pain questionnaire (NPQ) and markers of inflammation as assessed by various pro- and anti-inflammatory cytokines, as well as the eicosanoids PGE2 and LTB4. Results A significant group × time interaction was found for sensory pain scores (p  < 0.01). A Mann-Whitney test revealed that the change scores (3-month baseline) were significantly different between groups for IFN-y (U  = 13.0, p  = 0.01), IL-1β (U  = 14.0, p  = 0.01), and IL-2 (U  = 12.0, p  = 0.01). A Friedman test revealed the treatment group had a significant reduction in IFN-y (x 2  = 8.67, p  = 0.01), IL-1β (x 2  = 17.78, p  < 0.01), IL-6 (x 2  = 6.17, p  < 0.05), while the control group showed no significant change in any inflammatory mediator. A stepwise backward elimination multiple regression analysis showed that the change in sensory neuropathic pain was a function of the change in the proinflammatory cytokines IL-2 and IFN-y, as well as the eicosanoid PGE2 (R  = 0.689, R 2  = 0.474). Conclusions Overall, the results of the study demonstrate the efficacy of targeting inflammation as a means of treating neuropathic pain in SCI, with a potential mechanism relating to the reduction in proinflammatory cytokines and PGE2. Trial registration ClinicalTrials.gov, NCT02099890